Vortex suppression on high subsonic turbine blade via micro holes (30 Degree) / Mohd Hafiz Mohd Noh, Ahmad Hussein Abdul Hamid, and Koichi Moris - Mohd Noh, Mohd Hafiz; Abdul Hamid, Ahmad Hussein; Moris, Koichi (Universiti Teknologi MARA, 2022)
The vortex shedding of a turbine blade is suppressed by making a hole, connecting between the pressure side and suction side in the area of the trailing edge. Computational simulation has been done via numerical code by using Spalart-Allmaras turbulence model with Delayed Detached Eddy Simulation. The exit Reynolds number is 2.8 × 106 and the exit isentropic Mach number is 0.79. The size of the hole is 0.094D with a connecting angle of 30 degrees. The result shows that the vortex has successfully been suppressed at the turbine trailing edge and turbine wake area. The micro-hole is capable to reduce initial vortex formation which can be confirmed by the decrement of frequency peak and via observation of flow field vortex simulation.